Air–steam biomass gasification: Experiments, modeling and simulation. (15th February 2016) - Sharma, Shweta; Sheth, Pratik N.
Highlights: Experiments on downdraft gasifier are carried out for various equivalence ratios. The temperature and producer gas composition variation with time is presented. The effects of steam insertion directly in the reduction zone are studied. The effects of steam to biomass ratio on the producer gas composition are reported. Abstract: Biomass is one of the most widely available energy sources and gasification is as an efficient process of converting biomass into combustible gases by partial oxidation at high temperature. In order to increase the hydrogen content of the producer gas, steam is used along with air in a gasifier. In the present study, extensive experimental work is carried out in a downdraft gasifier using air and steam both and termed as air–steam gasification. Upon reaching the steady state conditions with air gasification, saturated steam is injected into the reduction zone of gasifier and its effects on gasifier performance is evaluated. The steam addition boosts the water gas shift reaction and increases the hydrogen content in the producer gas. The dynamic behavior of the gasifier in terms of the variation of composition of producer gas and zone temperatures with time is incorporated in the present study. The performance of gasification has been evaluated by varying the operating parameters like moisture content (0.015–0.042 wet basis), steam to biomass ratio (0.76–1.21) and equivalence ratio (0.1288–0.303). With the variation in the above parameters biomass consumption rate, composition of producer gas and cold gas efficiency is analyzed. Equilibrium model is developed to predict the composition of producer gas and calorific values. Component balances and energy balance are coupled with the equilibrium relations in the model. The developed model is validated using the experimental data. The effects of moisture content, equivalence ratio, and steam to biomass ratio on the composition are predicted.